Overhead Squat Assessment (Ohsa) - Senthil, P.; Swathi, Saina (Research Highlights in Disease and Health Research Vol. 3, 2023)
The overhead squat evaluation is a screening test that judges dynamic posture subjectively. The majority of dynamic posture evaluations use expensive laboratory techniques, which may not be applicable to all movement professionals and trainers in real-world contexts. Because the overhead squat evaluation is regarded as being extremely practical and time-efficient, knowledge of the dynamic posture assessment is required to both identify the altered movement patterns and to train the individuals. This chapter's major goal is to give various healthcare professionals a fundamental grasp of the overhead squat test technique, its grading system, prevalent symptoms of dysfunction found during the assessment, and its corrective exercises.